Chronic pancreatitis: issues remain unresolved - V. T. Ivashkin; K. V. Ivashkin; A. V. Okhlobystin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Key points. Article is devoted to one of the major syndromes of chronic pancreatitis — exocrine pancreatic insufficiency. Clinical symptoms of exocrine insufficiency: diarrhea with steatorrhea and flatulence are nonspecific and inconsistent. Laboratory diagnostics nowadays in our country is based on a single method — pancreatic elastase stool test which has low sensitivity and specificity, moreover it is characterized by low reproducibility. Thus, in practical situation it is reasonable to control both severity of disorders of pancreatic secretion, and efficacy of enzyme replacement therapy according to scores of trophological status of the patient both clinical (BMI), and laboratory (serum levels of prealbumin, retinol-binding protein, cholesterol, magnesium). Treatment should include high dose microgranulated enzymes in the form of capsules (the starting dose should be no less than 40 U of lipolytic activity per meal) as well as proton pump inhibitors. Replacement treatment should be life-long.